Intention to Scan QRIS Memediasi Trust dan Attitude terhadap Use Mobile Banking - Saputri, Nemshy Elfa; Susilowati, Endah (Universitas Gorontalo, 2025)
This study aims to examine how the intention to scan QRIS serves as a mediator between trust and attitude toward the use of mobile banking. A quantitative research approach was employed through the distribution of questionnaires. The population in this study consisted of students enrolled in the